Psyched out by numbers: Altruism and the dangers of methodolatry - Ispas, Alexa (Europe’s Journal of Psychology, 2007)
Try to remember the last time you helped someone. It may have been a relative, a friend, or a stranger on the street. Helping may have been easy, or may have involved considerable effort. The question is: why did you help? Was it to benefit the other person, or to benefit yourself? ‘Of course I helped to benefit the other person’, most people would say.